Penerapan Revolusi Mental Dalam Meningkatkan Kinerja Anggota Polres Hulu Sungai Selatan - Binsar Marpaung; Singgih Priono (STIA Bina Banua Banjarmasin, 2020)
This study aims to (1) find out the application of mental revolution in terms of attitude, character, temperament and character in improving the performance of South Hulu Sungai Police Resort. (2) identify the obstacles in the application of mental revolutions to improve. (3) find out solutions that can overcome obstacles in the application. The design of this study is based on a survey approach which is descriptive qualitative in nature. Data collected through interviews, observation and documentation. The analysis used in this study is qualitative. The results showed that (1) The application of a mental revolution in improving the performance of South Hulu Sungai Police Resort members was carried out optimally. Based on the results of the study showed that the existence of the application of the mental revolution seen a good attitude in accordance with what is expected by the police institution. For the application of the mental revolution seen from the nature carried out as part of Polri's tasks to be able to improve discipline so as to provide the best service to the community. To manage organizational member behavior and temperament that develops with a change in culture (mental revolution). Judging from the character in improving the performance of the South Hulu Sungai Police Resort to show the figure of the South Hulu Sungai Polress Member who is more empathetic to the community. This research is not fully said that the performance results can increase its members in a professional manner because there are still deficiencies that need to be addressed, especially regarding the elements of increasing member discipline owned, the number of work support facilities owned are still for operational purposes as well as service work targets that must be provided to local community community through the effectiveness of cooperation in accordance with management in the South Hulu Sungai Police Resort. (2) Constraints caused by lack of quality education and training, lack of inherent supervision and the need for welfare have not been fully provided properly. (3) solutions carried out by (1) improving the quality of education and training of members (2) carrying out supervision and (3) increasing welfare to members. Penelitian ini bertujuan untuk (1) mengetahui penerapan revolusi mental di lihat dari sikap, sifat, temperamen dan watak dalam meningkatkan kinerja Anggota Polres Hulu Sungai Selatan. (2) mengidentifikasi yang menjadi kendala dan. (3) mengetahui solusi yang dapat mengatasi kendala. Rancangan penelitian ini berdasarkan pendekatan kualitatif yang sifat penelitian ini adalah deskriptif kualitatif. Informan adalah semua Kasat di Polres dan key informan dalam penelitian ini adalah Kepala Bagian Sumda (Sumber Daya) dan Bagian Bina Mitra dan Bagian administrasi Polres Hulu Sungai Selatan. Data dikumpulkan melalui wawancara, observasi dan dokumentasi. Analisis yang digunakan dalam penelitian ini adalah kualitatif. Hasil penelitian menunjukan bahwa (1) Penerapan revolusi mental dalam meningkatkan kinerja Anggota Polres Hulu Sungai Selatan telah dilaksanakan secara optimal. Penerapan revolusi mental dilihat sikap yang baik sesuai dengan yang diharapkan oleh lembaga kepolisian. Dilihat dari sifat yang dilaksanakan sebagai bagian tugas Polri untuk lebih dapat meningkatkan kedisiplinan. Temperamen yang berkembang dengan perubahan kultur (revolusi mental). Dilihat dari watak dalam meningkatkan kinerja anggota Polres Hulu Sungai Selatan untuk menampilkan sosok lebih berempati kepada masyarakat. Penelitian ini tidak sepenuhnya dikatakan bahwa hasil kinerja dapat meningkatkan anggotanya secara profesional karenanya masih terdapat kekurangan yang perlu dibenahi terutama menyangkut unsur-unsur peningkatan disiplin anggota yang dimiliki, jumlah sarana pendukung kerja yang dimiliki masih untuk keperluan secara operasional serta sasaran kerja pelayanan yang harus diberikan kepada masyarakat. (2) Kendala disebabkan oleh kurangnya kualitas pendidikan dan pelatihan, kurangnya pengawasan melekat serta kebutuhan akan kesejahteraan belum sepenuhnya diberikan dengan baik. (3) solusi yang dilakukan dengan (1) peningkatan kualitas pendidikan dan pelatihan anggota (2) melakukan pelaksanaan pengawasan serta (3) peningkatan kesejahateran kepada anggota.